(untitled) (World Economics and Finance Bulletin, 2025)
This article examines the organization and improvement of inventory auditing in wineries. It analyzes the specific features of inventory accounting and auditing such as seasonality, natural loss rates, biochemical changes of raw materials, and batch-based production. Recommendations are proposed for implementing digital audit tools and technologies to ensure transparency of inventory movement and reliability of financial information.